Financial Resilience of Indonesian SMEs Amid Economic Uncertainty: The Roles of Accounting Information Quality, Financial Management Capability, and Strategic Agility - Muhammad Fajeri Siregar; Muhammad Hafis Akbar Nasution; Emi Uliyanty Boru Sidabutar; Veranda Panjaitan; Egy Juwita Tarigan (Manunggal Halim Jaya, 2026)
This study examines the financial resilience of Indonesian small and medium-sized enterprises amid economic uncertainty by focusing on the roles of accounting information quality, financial management capability, and strategic agility. The study aims to develop an integrated understanding of how these internal capabilities enable SMEs to anticipate financial pressures, maintain operational continuity, adapt resource allocation, and recover from disruption. A qualitative literature review method was employed by systematically identifying, selecting, comparing, and synthesizing peer-reviewed studies, publications, and institutional reports related to SME resilience, accounting information, financial management, strategic agility, digital transformation, and business sustainability. The findings indicate that accounting information quality functions as an early-warning and financial sensing mechanism by providing accurate, relevant, complete, and timely information for decision-making. Financial management capability translates such information into budgeting, liquidity control, working-capital management, debt evaluation, and risk mitigation. Strategic agility strengthens resilience by enabling rapid decisions, market adjustment, innovation, and resource reconfiguration. The study further finds that these three capabilities are complementary rather than independent. Financial resilience is strongest when reliable information, disciplined financial practices, and adaptive strategies operate simultaneously. The resulting framework contributes theoretically to dynamic capability and resource-based perspectives while offering practical guidance for SME owners, financial institutions, and policymakers.